Nutritional Value and Physico-Chemical Characteristics of Apple Snail Pila globosa (Swainson) and Lymnaea luteola Lamark (Bangladesh Journal of Scientific and Industrial Research, 2012)
The physico-chemical characteristics, lipids, protein, fat, moisture and ash of P. globosa and L.luteola were studied. The percentage of oil content found were 2.30 ± 0.29 and 1.61 ± 0.12 in meat of P. globosa and L. luteola. The protein and fat content of P. globosa were 33.81% and 1.80% whereas 22.71% and 1.49% in L. luteola. The moisture content were 75.31% and 78.96% in P. globosa and L. luteola respectively. The total lipid extracts were fractionated into three major lipid groups neutral lipids, glycolipids and phospholipids by silicic acid column chromatography. The glycolipid were averaged to 57.39% and 57.24% of the weight of the lipid applied in L. luteola and P. globosa. The percentage composition of fatty acids were found in the form of oleic 19.46 ± 0.33, lauric 13.23 ± 0.73, palmitic 16.56 ± 0.41 in L. luteola and 20.37 ±1.38, 14.30 ± 1.06 and 18.52 ± 1.10 in P. globosa respectively. Keywords: P. globosa; L .luteola; Lipid; Protein; Moisture. DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9604 BJSIR 2011; 46(4): 539-542